The meaning of Paul for today - Dodd, Charles Harold, 1884-1973 (London, UK Collins, 1920)
Includes bibliographical references and index.
Keywords: Bible. N.T. Epistles of Paul -- theology; Paul, the Apostle, Saint -- theology